Fibre optic interconnecting devices and passive components. Basic test and measurement procedures. Examinations and measurements. Angular misalignment between ferrule bore axis and ferrule axis for cylindrical ferrules Part 3-54, (6th September 2019) - British Standards Institution,
No abstract available